2014
DOI: 10.1148/radiol.13130801
|View full text |Cite
|
Sign up to set email alerts
|

Low-Risk Prostate Cancer: The Accuracy of Multiparametric MR Imaging for Detection

Abstract: Detection of prostate cancer in patients with clinically low-risk cancer with multiparametric MR imaging is highly accurate, and larger cancer volume and higher Gleason grade are associated with higher detection accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…9 Dynamic contrast-enhanced computed tomography (CT) has demonstrated its ability for the noninvasive assessment of angiogenesis by determining functional parameters of tissue microcirculation in different malignant lesions. 15Y21 There are also potential roles for DCE CT in prostate cancer, such as the initial tumor assessment, follow-up, and monitoring of therapy response in patients with contraindications to MRI, such as pacemakers or ferromagnetic vascular coils.…”
Section: Y14mentioning
confidence: 99%
See 2 more Smart Citations
“…9 Dynamic contrast-enhanced computed tomography (CT) has demonstrated its ability for the noninvasive assessment of angiogenesis by determining functional parameters of tissue microcirculation in different malignant lesions. 15Y21 There are also potential roles for DCE CT in prostate cancer, such as the initial tumor assessment, follow-up, and monitoring of therapy response in patients with contraindications to MRI, such as pacemakers or ferromagnetic vascular coils.…”
Section: Y14mentioning
confidence: 99%
“…15Y21 There are also potential roles for DCE CT in prostate cancer, such as the initial tumor assessment, follow-up, and monitoring of therapy response in patients with contraindications to MRI, such as pacemakers or ferromagnetic vascular coils. 9,22Y25 The prostate, however, is comparably difficult to assess with CT-perfusion (CTP) because of artifacts from neighboring pelvic bones and the usually small volume of prostate cancer as well as coexisting benign prostatic hyperplasia and chronic prostatitis. On the other hand, several tumor spots of varying grades may coexist or even diffusely infiltrate the prostate parenchyma rather than form circumscribed compounds.…”
Section: Y14mentioning
confidence: 99%
See 1 more Smart Citation
“…[34][35][36] Indeed, MRI is known to be poor at detecting low-grade, low-volume cancer, lacking sensitivity even in cases where the predominant Gleason pattern is 4, but the cancer volume is <0.2 cm 3 . [36][37][38] These factors reflect the need for further advances in imaging to detect such lesions. We found that anterior lesions were more likely to be missed than lesions elsewhere within the prostate, which reflects the known difficulty in identifying cancer within the heterogeneous transition zone (TZ) and fibromuscular stroma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported a sensitivity and specificity by MRI of 84.2 and 66.6% respectively in the detection of clinically low-risk PCa with Gleason scores less than or equal to 6. In contrast, cancers with higher Gleason grades, i.e., clinically significant tumors, had a detection accuracy of about 90 % (Kim et al 2014) and a negative predictive value of up to 95 % (Arumainayagam et al 2013). Other research groups found diffusion-weighted imaging (DWI) at 3 Tesla (T) alone detecting significant PCa with a sensitivity and specificity ranging from 89 to 91 % and 77 to 81 %, respectively (Bains et al 2014).…”
Section: The Role Of Magnetic Resonance Imaging (Mri) In the Diagnosimentioning
confidence: 99%